Strategi implementasi blended librarian dalam pemenuhan kebutuhan informasi pemustaka dan sivitas akademika di perguruan tinggi pada era digital - Hidayah, Nurul (Maliki Interdisciplinary Journal, 2023)
Information and Communication Technology In today's digital era, it has dominated in various kinds of daily activities. The challenge of librarians today is no longer with libraries of other institutions but with the sophistication of information technology that without us realizing it has changed the pattern of behavior of the information society in the current era. The development that does not feel very rapid makes people tend to search for information through websites from search engines, the mindset of people who want to get information quickly makes the number of reading interest of the information community, especially students, gradually decrease. Higher education librarians are required to be adaptive to the phenomena that are happening, the concept of service activities and the automation system of library materials need to be changed. By starting to implement blanded librarians which is a renewal of the function of librarians who are able to combine the duties as traditional librarians and collaborate advances in information and communication technology in it. Librarians must be active in knowing what information is currently trending among the public. The implementation of a new concept in the library will inevitably encounter certain obstacles, these obstacles can come from users, library leaders and librarians themselves. So there needs to be a special strategy so that the concept can be applied properly. In supporting the implementation of the Tri Dharma of Higher Education, namely Education, service and research requires the role of librarians who are able to utilize technology and are able to answer all questions and complaints of users who are net generation.